Emergency department visits: Why adults choose the emergency room over a primary care physician visit during regular office hours? - Rocovich, Courtney (Second Affiliated Hospital of Zhejiang University School of Medicine, 2012)
BACKGROUND: It has been estimated that up to one third of all emergency department (ED) visits may be “inappropriate” or non-emergent. Factors that have been speculated to be associated with non-emergent use have been noted to include low socioeconomic status, lack of access to primary care, lack of insurance, convenience of “on demand care” and the patient’s individual perception of their complaint urgency. The objective of this study is to identify the reasons contributing to self-perceived non-emergent adult emergency department visits during primary care physician office hours of operation. METHODS: This study was a single-center, descriptive study with questionnaire. The questionnaire was collected from patients meeting exclusion/inclusion criteria who were triaged into an acute or fast track part of the emergency department during regular business hours on Monday through Friday, 8:00 am-5:00 pm during the months of July 2011 and August 2011. Questionnaire data were categorical and summarized using counts and percentages. Data collected included patient demographics, information about the patient’s primary care provider, and information about the emergency department visit in question. All responses were compared among patients with visits considered to be non-emergent to those considered to be emergent by using individual chi-square tests. RESULTS: There were 262 patients available for the study. The patients were grouped according to their perception of the severity of their complaints. Roughly half of the patients placed themselves into the non-emergent category (n=129), whereas the other half of the patients categorized themselves into the emergent group (n=131). There were statistically significant differences in marital status and employment status between the two groups. It was found that 61.5% of the non-emergent patients were single, while 58.3% of the emergent patients were married. In the non-emergent group, 59.7% were unemployed, but in the emergent group 60.3% were employed (P<0.05). However, no other factors were significantly different. CONCLUSIONS: Our study did not identify a statistically significant factor to the reasoning behind why patients choose the emergency department over a primary care physician during regular office hours. The only significant demographic indicating who was more likely to make this choice during the specified time frame was being single and employed with perceived non-emergent complaint. Patients without insurance and/or without a primary care physician were no more likely to visit the emergency department with a self-perceived non-emergent issue than patients with insurance and/or with an established primary care physician.